Pharmacological mechanisms and animal models of cognition. - Dawson, G; Heyes, C; Iversen, S (1992)
Requirements for an effective animal model of cognition are discussed with special reference to the cholinergic hypothesis of Alzheimer's disease. It is argued, with reference to research on vasopressin and ACE inhibitors, that many putative animal models of cognition lack predictive clinical validity because they either confound the effects of cognitive and arousal processes, or fail to model a specific component of cognitive functioning. A survey of recent research on the cholinergic hypothesis illustrates how these weaknesses can be overcome. Studies involving scopolamine and basal forebrain excitatory amino acid lesion models of the cholinergic deficit in Alzheimer's disease have employed a delayed-matching-to-position test in rodents which, unlike passive avoidance, allows the effects of memory and attentional variables to be distinguished. In combination with recent human studies, these experiments suggest that the cholinergic system has a major role in executive control of attentional resources, and lead to the recommendation of a 'top down' strategy in the investigation of neurochemical processes and pharmacological mechanisms underlying cognition.